Предмет:
МатематикаАвтор:
аноним1. Заданы три числа: A(n) = X + 3, A(n + 1) = 2 * X - 1, A(n + 2) = X² - 3;
2. Пусть они являются членами арифметической прогрессии, тогда:
A(n + 1) - A(n) = D;
(2 * X - 1) - (X + 3) = X - 4 = D;
A(n + 2) - A(n +1) = D;
(X² - 3) - (2 * X - 1) = X² - 2 * X - 2 = D;
3. Приравниваем:
X - 4 = X² - 2 * X - 2;
X² - 3 * X + 2 = 0;
(X² - 2 * X) - (X - 2) = X * (X - 2) - (X - 2) =
(X - 2) * (X - 1) = 0;
4. X1 = 2, D = X - 4 = 2 - 4 = -2;
A(n) = X + 3 = 2 + 3 = 5;
A(n +1) = 2 * X - 1 = 2 * 2 -1 = 3;
A(n +2) = X² - 3 = 2² -3 = 1;
5. X2 = 1, D = X - 4 = 1 - 4 = -3;
A(n) = X + 3 = 1 + 3 = 4;
A(n +1) = 2 * 1 - 1 = 2 * 1 -1 = 1;
A(n +2) = X² - 3 = 1² -3 = -2.
Ответ: 1) X1 = 2, D = -2; 2) X2 = 1, D = -3.
Автор:
candy45Добавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть